2016
DOI: 10.1016/j.addbeh.2016.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Polytobacco, marijuana, and alcohol use patterns in college students: A latent class analysis

Abstract: Limited research has examined polysubstance use profiles among young adults focusing on the various tobacco products currently available. We examined use patterns of various tobacco products, marijuana, and alcohol using data from the baseline survey of a multiwave longitudinal study of 3418 students aged 18-25 recruited from seven U.S. college campuses. We assessed sociodemographics, individual-level factors (depression; perceptions of harm and addictiveness,), and sociocontextual factors (parental/friend use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 48 publications
7
50
0
2
Order By: Relevance
“…The items demonstrate face validity, and these subscales demonstrated convergent and discriminant validity, which is further elaborated upon below. The new measure largely reflects the literature that informed our conceptual framework (Cohn et al, 2015; Haardörfer et al, 2016; Piko et al, 2007; Ramo et al, 2013; Rath et al, 2012; Richardson et al, 2014; Schauer et al, 2015; Schauer et al, 2016; Simons et al, 2000; Sutfin et al, 2009; Wills et al, 1999), as well as the constructs and associations involved in the Social Cognitive Theory (Bandura, 1998, 2004). Moreover, it is important to note that the addition of these subscales to the regression models predicted nicotine dependence and days of marijuana use, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The items demonstrate face validity, and these subscales demonstrated convergent and discriminant validity, which is further elaborated upon below. The new measure largely reflects the literature that informed our conceptual framework (Cohn et al, 2015; Haardörfer et al, 2016; Piko et al, 2007; Ramo et al, 2013; Rath et al, 2012; Richardson et al, 2014; Schauer et al, 2015; Schauer et al, 2016; Simons et al, 2000; Sutfin et al, 2009; Wills et al, 1999), as well as the constructs and associations involved in the Social Cognitive Theory (Bandura, 1998, 2004). Moreover, it is important to note that the addition of these subscales to the regression models predicted nicotine dependence and days of marijuana use, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We also drew from the literature regarding motives for tobacco and marijuana use, respectively (Piko, Wills, & Walker, 2007; Simons, Correia, & Carey, 2000; Wills, Sandy, & Shinar, 1999), the limited literature regarding reasons for co-use (Ramo, Liu, et al, 2013; Schauer et al, 2016) as well as our qualitative findings, and the literature regarding patterns and trajectories of marijuana-tobacco use and polysubstance use more broadly (Cohn et al, 2015; Haardörfer et al, 2016; Rath, Villanti, Abrams, & Vallone, 2012; Richardson, Williams, Rath, Villanti, & Vallone, 2014; Schauer et al, 2015; Sutfin et al, 2009). In particular, outcome expectancies are a central component of Social Cognitive Theory (Bandura, 1998, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that many of the participants in the studies reviewed here not only engaged in marijuana use, but also in a constellation of substance use and illicit behaviors. Marijuana use is associated with alcohol use (Haardörfer et al, 2016;Haas et al, 2015) and drug use (Moss et al, 2014;Palamar et al, 2015), which further suggests this might be true. It has been suggested that impulsivity is a transdiagnostic risk factor, making intervening on impulsivity of higher clinical relevance, in that interventions designed to mitigate impulsivity's effects are more likely to influence a wide range of substance-related and behavioral addictions, not just marijuana use.…”
Section: Present Findings Have Significant Implications For Marijuanamentioning
confidence: 95%